Role of the p38 mitogen‐activated protein kinase signaling pathway in estrogen‐mediated protection following flap ischemia‐reperfusion injury. (October 2016) - Ju, JiHui; Wu, JianLong; Hou, RuiXing
Abstract : Ischemia‐reperfusion (I/R) injury often occurs during skin flap transplantation and results in tissue damage. Although estrogen treatment significantly alleviates this I/R injury‐induced damage, the detailed molecular mechanism is not clear. In this study, a superficial epigastric artery flap I/R injury model was created in adult Wistar rats. Severe necrosis was observed in skin tissue after I/R injury. Histological examination of skin tissue revealed that I/R injury damages skin structure and results in neutrophil infiltration. Inflammation‐related parameters, including neutrophil count, tumor necrosis factor‐α, and interleukin‐10 levels, were increased due to I/R injury. These pathological phenomena were reduced by estradiol treatment. Further investigation found that I/R injury triggers the p38 mitogen‐activated protein kinase (p38‐MAPK) pathway. The expression levels of p38‐MAPK and phosphorylated p38‐MAPK were increased after I/R injury. Estradiol increased the expression level of MAPK phosphatase‐2, a putative phosphatase of p38, and reduced the levels of p38‐MAPK and phosphorylated p38‐MAPK. These results suggest that estradiol can improve skin flap survival, possibly by inhibiting neutrophil infiltration and the expression of p38‐MAPK. This study provides an explanation for how estrogen alleviates I/R injury‐induced damage that occurs during skin flap transplantation. In a rat pathological model, I/R injury leads to skin necrosis, skin structure damage, neutrophil infiltration, and inflammatory cytokine secretion, which are probably downstream effects of activation of the p38‐MAPK pathway. On the other hand, estradiol treatment triggers the expression of MAPK phosphatase‐2, a putative phosphatase of p38‐MAPK, and reduced all examined pathological phenomena. Therefore, estrogen may reduce the deleterious effect of I/R injury on skin flap transplantation through modulating the p38‐MAPK pathway.